Feminist Perspective of Life’s Struggle: A Literature Review of the Movie Little Woman (2019) - Samad, Pratiwi; Paris, Nirma (Universitas Sulawesi Barat, 2024)
This study delves into the challenges contemporary women face, particularly in negotiating societal expectations, spiritual support in relationships, and the balance between education, career, and marriage. Through an analysis of the characters Jo and Amy in Greta Gerwig's